Konsep Prosedur Contingency Penanggulangan Bencana Alam dalam Pelayanan Lalu Lintas Penerbangan di Perum LPPNPI Distrik Manado - Idyaningsih, Nining; Bahrawi, Ahmad (Politeknik Penerbangan Makassar, 2020)
In providing flight traffic services, ATC (Air Traffic Controller) officers are required to be able to provide services in accordance with procedures so that flight safety can be guaranteed. This study aims to draft a contingency plan procedure in accordance with the potential for natural disasters that can occur, namely volcanic eruptions and earthquakes in the LPPNPI Public Corporation of Manado District. The research method was carried out in a qualitative and quantitative description to conceptualize the natural disaster management contingency procedure for air traffic services in the Perum LPPNPI Manado District based on document 9426 and Annex 11. The results showed a high level of safety when volcanic and earthquake activities occurred if the Manado District LPPNPI had a contingency plan procedure as a guide. It is recommended that these guidelines remain a reference in air traffic services when disruptions occur due to volcanic eruptions and earthquakes